The oral Storytelling: An alternative for the development of an educational experience with gender perspectives (2015)
The work presented here explains the nature of teaching experience in the University of Medical Sciences of Santiago de Cuba, referring to the creation of an orality official chair with a focus on gender. It aimed to contribute to the management and development of practices and social processes of education/communication and the educational processes resulting from this; as well as develop a critical reflection on the role of women in the narrative experience of everyday life and in the rescue of the word in different educational and sociocultural contexts. During the implementation of the official Chairs organized by the development fields: ``History of the University of Medical Sciences´´, “Oral storytelling and its interdisciplinary relationship”,“The narrative medicine”,“The oral storytelling as an art and conduct-expressive behaviour”: The mainstreaming of the gender approach appears as a methodological strategy, since the systematic approach, in order to make possible the development of the thought and communicative basic skills based on the oral storytelling. In the conclusions, it expresses how the achievement of these aims has passed, for a set of activities in the teaching, research and extension areas. Not only the theoretical aspects took part, there was also a sharing reflection in the construction of a sociocultural experience, that allowed an exchange of knowledge,experiences and participation through the oral storytelling planned as an open space for the learning process.